2015
DOI: 10.3892/etm.2015.2650
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of propranolol in the treatment of hemangioma and changes in serum VEGF, bFGF and MMP-9

Abstract: Abstract. The aim of this study was to observe the clinical efficacy and safety of propranolol in the treatment of hemangioma, and to reveal its possible mechanism. A total of 129 cases of proliferative hemangioma were divided into two groups: i) Treatment (n=97), in which the patients received oral propranolol therapy and ii) observation (n=32), in which the patients underwent clinical observation. The changes in the hemangiomas were noted and compared between the two groups. In addition, the heart rate, bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
2
17
0
4
Order By: Relevance
“…Furthermore they showed that PRO treatment could reduce the rate of tumour growth and infiltration in vivo. A similar inhibition of the upregulation of MMP-2 and MMP-9 by PRO has also been reported in nasopharyngeal carcinoma [59], pancreatic cancer [50, 53], gastric adenocarcinoma [66], melanoma [106], prostate cancer [107] and of MMP-9 in medulloblastoma [108] and infantile hemangioma [109110]. …”
Section: Mechanisms Of Actionsupporting
confidence: 69%
“…Furthermore they showed that PRO treatment could reduce the rate of tumour growth and infiltration in vivo. A similar inhibition of the upregulation of MMP-2 and MMP-9 by PRO has also been reported in nasopharyngeal carcinoma [59], pancreatic cancer [50, 53], gastric adenocarcinoma [66], melanoma [106], prostate cancer [107] and of MMP-9 in medulloblastoma [108] and infantile hemangioma [109110]. …”
Section: Mechanisms Of Actionsupporting
confidence: 69%
“…Wu et al. (2015) investigated the effectiveness of propranolol treatment in IH and changes in the serum levels of VEGF, bFGF, and MMP‐9. The authors examined 129 cases, 97 of which were treated with oral propranolol; 32 received no treatment.…”
Section: Mechanism Of Action Of Beta‐blockersmentioning
confidence: 99%
“…The authors speculated that the effects of propranolol on IH might be due to the reduction of VEGF and eNOS. Wu et al (2015) [ 48 ] investigated the effectiveness of propranolol treatment in IH and changes in the serum levels of VEGF, bFGF, and MMP-9. The authors examined 129 cases, 97 of which were treated with oral propranolol; 32 received no treatment.…”
Section: Mechanism Of Action Of Beta-blockersmentioning
confidence: 99%
“…Wu et al. (2015) untersuchten die Wirksamkeit der Therapie des IH mit Propranolol und die Veränderungen der Serumspiegel von VEGF, bFGF und MMP‐9. Die Autoren werteten 129 Fälle aus, 97 Patienten erhielten Propranolol p.o., 32 keine Behandlung.…”
Section: Wirkmechanismus Der Betablockerunclassified